Concept of Correlation between Active Learning and Employability Skills in TVET - Rohanai, Reyanhealme; othman, hasyamuddin; Mat Daud, Khairul Azhar; Omar, Nurul Huda; Ismail, Mohd Erfy; Sulaiman, Abdullah (Online Journal for TVET Practitioners, 2020)
An Industrial Revolution 4.0 promoted by Malaysian government entitles the rapid growth of manufacturing sector thus promotes a multi-level of workforce and skilled workforce needed to satisfy the rapid technological development application. The challenges arise on preparing the individuals to meet with the current business and the students need to be prepared in such way satisfied the business expectations. Looking into this situation, this paper aims to study the concept of correlation between active learning and employability skills in Technical and Vocational Education and Training (TVET). The study assumes that there is positive relationship between employability skills and active learning in improving student’s quality. The method of study involves documentation analysis on previous research to prove the importance of employability skills enhancing student’s quality and the effectiveness of active learning; Problem-Based Learning (PBL) method in preparing the students to meet the expectations. The main findings of this study claimed that there was a positive relationship between employability skills and PBL method. Result acknowledge that PBL has the solutions to help students develop employability skills and behavior. As all ideas and suggestion in this paper was cited as the understanding from previous study findings and arise from the reviews of expertise. The recommendation on future study is crucial to justify deeply the effectiveness of this correlational concept by performing experimental study to provide a concrete evidence towards this understanding.